A comprehensive study of product distributions and coke deposition during catalytic cracking of vacuum gas oil over hierarchical zeolites. Issue 4 (April 2023) - Fals, Jayson; Toloza, Carlos A.T.; Puello-Polo, Esneyder; Márquez, Edgar; Méndez, Franklin J.
Abstract: In this study, zeolites (Z) were used as catalysts in the cracking of a Colombian vacuum gas oil (VGO), with a focus on product distribution and coke deposition. The catalytic tests were carried out in a MAT-type reactor under typical conditions. The zeolites were subjected to alkaline treatment with NaOH at concentrations ranging from 0.05 to 0.4 mol/L, resulting in the creation of several samples (Z-0.05, Z-0.10, Z-0.20, Z-0.30 and Z-0.40) that were then hydrothermally stabilized (Z-0.05-M, Z-0.10-M, Z-0.20-M, Z-0.30-M and Z-0.40-M) to increase mesoporosity and reduced crystallinity. The increase in mesoporosity was accompanied by an improvement in acidity. Despite Z-0.30-M having higher acidity, Z-0.00-M and Z-0.10-M exhibited the highest activity due to their high crystallinity and microporosity, yielding the highest gas yields. Gasoline was the main product, with maximum yields exceeding 30%. Z-0.20-M produced more aromatic and olefin compounds than the others, resulting in higher quality gasoline. Coke formation followed the trend: Z-0.00-M < Z-0.10-M < Z-0.20-M < Z-0.30-M. The higher intracrystalline mesoporosity in the zeolites favored the formation of a more condensed coke.